Effect of increasing standardized ileal digestible valine to lysine ratio on growth performance of 15- to 25-lb nursery pigs - Nemechek, J.E.; Usry, J.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 294 nursery pigs (PIC TR4 × 1050, initially 15.1 lb, 3 d postweaning) were used in a 28-d growth trial to evaluate the effects of increasing standardized ileal digestible valine:lysine ratio on growth performance. Pigs were allotted to 1 of 6 dietary treatments. A 2-phase diet series was used, with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. All diets were in meal form. The 6 standardized ileal digestible (SID) valine:lysine ratios were 57.4, 59.9, 62.3, 64.7, 67.2, and 69.6%. The SID lysine level of the diet was 1.30%. There were 7 pigs per pen and 7 pens per treatment. Pigs and feeders were weighed on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. From d 0 to 14, ADG and ADFI increased (quadratic, P < 0.01) as the valine:lysine ratio increased from 57.4 to 64.7%, with little improvement observed thereafter. Feed efficiency improved (linear, P < 0.02) with increasing valine:lysine ratio, but like ADG and ADFI, there was little improvement observed beyond the 64.7% valine:lysine ratio. From d 14 to 28, when the common diet was fed, there were no differences (P > 0.27) in ADG and ADFI; however, F/G became poorer (quadratic; P < 0.02) in pigs previously fed increasing valine:lysine ratio. The linear response in ADG and ADFI from Phase 1 carried over to the overall data (d 0 to 28), resulting in increased (linear; P < 0.003) ADG and ADFI with increasing valine:lysine ratio; however, no improvement was observed beyond the 64.7% valine:lysine ratio. There were no differences (P > 0.20) in overall F/G. Therefore, a minimum valine:lysine ratio of 64.7% was required for optimal growth of 15- to 25-lb pigs.
Keywords: Swine; Amino acid ratio; Amino acid requirement; Lysine; Valine